Society, paradigms & intellectuals - Carranza Elguera, Víctor (2019)
The objectives of this paper are to explore and describe how social relations sustain the creation of particular paradigms and those of their own intellectuals. In this sense, it is relevant to show situations in which the economic and political interests of the state powers demanded the cultural domain to strengthen social cohesion. For this reason, historical cases, that explain the causal relationship between religion and morality, are presented. These causal relations, formalized at the level of dogma, inhibited the creative development of knowledge and, therefore, the economy and politics. We warn that the dogmatic culture, which dominated and continues to dominate the global social panorama, could not avoid dissidence. In the historical route of this dissidence, in favour of the reason and the truth, heretics will be pointed out, also free thinkers and intellectuals. A key question: what is the margin of autonomy of Peruvian intellectuals to recreate the «regimes of truth» that become hegemonic governments in our society?